If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(g + -14) = 11 Reorder the terms: 0.5(-14 + g) = 11 (-14 * 0.5 + g * 0.5) = 11 (-7 + 0.5g) = 11 Solving -7 + 0.5g = 11 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 0.5g = 11 + 7 Combine like terms: -7 + 7 = 0 0 + 0.5g = 11 + 7 0.5g = 11 + 7 Combine like terms: 11 + 7 = 18 0.5g = 18 Divide each side by '0.5'. g = 36 Simplifying g = 36
| .5(g-14)=1 | | 1/3n+5=19/3 | | -1/3a+9=7 | | 6+5/6k=16 | | 3w+7/9=185/99 | | 4t-4=-5 | | -3/5a+4/5=23/20 | | 6+7n=89/9 | | 11-3x=-176 | | 5(g-14)=1 | | 5+5/7x=40/7 | | 3-6n=-63 | | 2/5t-4/5=-17/30 | | 5a+2/3=-8/3 | | 3b+4=34 | | 7w+8=10/3 | | 2/3x+9=17 | | 2/5a+8=64/5 | | 2/5x-5=-143/30 | | 2/3n+8=58/7 | | 5w-6/7=-41/7 | | 1/3m-9=-163/18 | | -1/3b+3/5=44/15 | | 3/4+6t=15/4 | | 20-4z=5z-35 | | 4w+1=-1 | | .10(s+200)=55 | | 6a+3/10=29/5 | | -3/4t+8=347/40 | | -1/3w+5=4/3 | | -8+2/3a=-116/15 | | n-8=-17/2 |